Breast-Conserving Surgery in a Young Man - Case Report - Silva, André; Seabra, Joana; Junior, Arymar; Ferreira, Pedro; Branco, Luís; Rigueira, Manuel Vítor; Cortez, Luís (Brazilian Journal of Case Reports, 2022)
Accounting for less than 1% of all breast cancer cases, male breast cancer (MBC) is a rare disease. Unlike female breast cancer, there are no randomized controlled trials to confirm the safety of breast-conserving surgery (BCS). Additionally, male patients have poor radiation therapy (RT) compliance after BCS, which raises concern about curative treatment of this patients. Therefore, BCS is less used in the treatment of these patients. The authors report a case of a 35-year-old male with the diagnosis of neoplasm of uncertain behavior of the breast (NUnBB) with raised suspicion on breast imaging studies. He was submitted to excisional biopsy of the lesion, and the pathologist examination showed a luminal B invasive carcinoma with free margins. Due to this postoperative diagnosis, he was submitted to axillary lymph node sampling that was negative for malign cells. The final pathology staging was pT1bpN0cM0. He was referred to oncology consultation for follow-up and adjuvant therapy with chemotherapy, RT, monoclonal antibody, and hormonotherapy. He remains free of disease to date, at 36 months follow-up. This case report describes a male patient treated with BCS with good oncologic results and highlights the need to build evidence-based research that support treatment recommendations in MBC.